Mary R. Musgrove letter to Thomas H. Kent regarding winter bird sightings, December 16, 1982 - Musgrove, Mary R.et al (1982)
Letter from Mary R. Musgrove to Thomas H. Kent regarding winter bird sightings, December 16, 1982. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1982-1983. Epson - sheet feed